2016
DOI: 10.24200/sci.2016.3981
|View full text |Cite
|
Sign up to set email alerts
|

MCM-41-SO3H-catalyzed synthesis of highly substituted 3-amino-imidazo[1,2-a]pyridines or pyrazines via the Groebke-Blackburn-Bienaymé multicomponent reaction under grinding conditions at ambient temperature

Abstract: A highly e cient method, which is environmentally-friendly, has been developed by a sequential one-pot, three-component reaction between isocyanides, aldehydes, and 2-aminopyridines or 2-aminopyrazines under solvent-free and grinding conditions at room temperature in the presence of nano-ordered MCM-41-SO3H.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Javanshir et al [40] have reported a three-component, one-pot, Groebke-Blackburn-Bienayme reaction for the preparation of substituted 3-aminoimidazo[1,2-a]pyridines or pyrazines in the presence of nano-ordered MCM-41-SO 3 H as hybrid catalyst (Figure 3). High acid strength of Brønsted acid sites in the catalyst explained the superior behaviour of this catalyst over others like Zn-MCM-41, Fe-MCM-41, and Al-MCM-41.…”
Section: Multicomponent Reactions (Mcrs)mentioning
confidence: 99%
“…Javanshir et al [40] have reported a three-component, one-pot, Groebke-Blackburn-Bienayme reaction for the preparation of substituted 3-aminoimidazo[1,2-a]pyridines or pyrazines in the presence of nano-ordered MCM-41-SO 3 H as hybrid catalyst (Figure 3). High acid strength of Brønsted acid sites in the catalyst explained the superior behaviour of this catalyst over others like Zn-MCM-41, Fe-MCM-41, and Al-MCM-41.…”
Section: Multicomponent Reactions (Mcrs)mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] By controlling the assembly or growth processes, different types of products with various structures, morphologies, or particle sizes can be produced. 12,13,[15][16][17][18][19][20][21] Periodic mesoporous organosilicas (PMOs) were rst reported in 1999 by Inagaki, 22 Ozin, 23 and Stein. 24 They are a class of materials synthesized via a sol-gel process from an organobridged alkoxysilane in the presence of a surfactant.…”
Section: Introductionmentioning
confidence: 99%